Electric, thermoelectric and magnetic characterization of γ-Fe2O3 and Co3O4 nanoparticles synthesized by facile thermal decomposition of metal-Schiff base complexes. (March 2018) - Ibrahim, E.M.M.; Abdel-Rahman, Laila H.; Abu-Dief, Ahmed M.; Elshafaie, A.; Hamdan, Samar Kamel; Ahmed, A.M.
Graphical abstract: Highlights: Fe and Co oxide NPs were prepared from Schiff base complexes as new precursors. The electrical conduction in Fe and Co oxide NPs is governed by hopping processes. Co3 O4 NPs show weak ferromagnetic ordering at room temperature. γ-Fe2 O3 NPs have superparamagnetic behavior. Abstract: Using novel compounds for synthesis of metal oxide nanomaterials can tune their physical properties due to the associated variation in the shape, size and crystallinity. In this work, γ-Fe2 O3 and Co3 O4 nanoparticles were successfully prepared by a facile thermal decomposition route, employing [Fe(C32 H22 N4 O2 )]·2H2 O and [Co(C16 H11 N3 O4 )]. 1 2 H2 O complexes, respectively as new precursors. The x-ray diffraction and high resolution transmission electron microscopy investigation confirmed that the materials consist of highly pure spinel γ-Fe2 O3 and Co3 O4 nanoparticles with average size of ∼ 9 and 30 nm, respectively. The electrical conduction is governed by the hopping mechanism. The thermoelectric power measurements confirmed that Co3 O4 nanoparticles are non-degenerate semiconductor with Fermi energy ∼1.21 eV while γ-Fe2 O3 nanoparticles showed a degenerate to non-degenerate transition. The Co3 O4 nanoparticles showed a weak ferromagnetic ordering that could be attributed to uncompensated surface spins due to finite-size effects. But γ- Fe2 O3 NPs show superparamagnetic behavior at room temperature.